Nakae Ushikichi in China : - Fogel, Joshua A. (Council on East Asian Studies, Harvard University : Distributed by Harvard University Press, 1989)
In the first full-length study in English of the life and thought of Nakae Ushikichi, Joshua A. Fogel tells the strange story of this cocky, indolent carouser who became a disciplined scholar and passionate advocate of the worth of all humanity. Fogel examines Nakae's Sinological work in the context of his wide reading in German philosophy, Western historiography, and classical Chinese sources. He also translates Nakae's wartime diary.